METHODOLOGY OF COST-UTILITY ANALYSIS IN PHARMACOECONOMICSTUDIES - R. I. Yagudina; I. V. Sorokovikov (Фармакоэкономика, 2015)
pharmacoeconomic cost-utility analysis – CUA is at third place by popularity (10% of studies) among studies of pharmacoeconomic analysis. Main stages of these trials are as follows: cost analysis, utility analysis and results assessment. Each of these stages may have impact on theend data reliability. The results of analysisis CUR coefficient (ICUR), reflecting cost value on utility unit. Correct assessment of analysis results may increase effectiveness of health care budget allocationand reveal more effective and appropriate treatment alternatives. All stages of cost-utility analysis and decision making algorithm are presented in the article.